2020
DOI: 10.1186/s41231-020-00055-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of resistance exercises and nano-curcumin on synovial levels of collagenase and nitric oxide in women with knee osteoarthritis

Abstract: Background: Osteoarthritis is the most common joint damage that leads to cartilage destruction, pain, and disability. The aim of this study is to investigate the effects of resistance exercises and Nano curcumin supplementation on synovial levels of collagenase-2 and NO in patients with knee osteoarthritis. Methods: Forty women with primary knee osteoarthritis were divided into four groups including control, exercise, supplementation, and supplementation /exercises. The resistance exercise group performed exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Furthermore, CUR-loaded PLGA NP treatment during OA inhibited the expression of iNOS, which is an inflammation-induced enzyme that catalyzes the production of the proinflammatory mediator nitric oxide (NO), further demonstrating its anti-inflammatory effects. Several in vivo and in vitro studies [36,37] have shown that CUR treatment reduces iNOS production in various inflammatory diseases. Most recently, Cheragh-Birjandi et al [37] postulated that 10 Mediators of Inflammation in turn promote the expression of a variety of matrixdegrading enzymes, including metalloproteinases (MMPs) [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, CUR-loaded PLGA NP treatment during OA inhibited the expression of iNOS, which is an inflammation-induced enzyme that catalyzes the production of the proinflammatory mediator nitric oxide (NO), further demonstrating its anti-inflammatory effects. Several in vivo and in vitro studies [36,37] have shown that CUR treatment reduces iNOS production in various inflammatory diseases. Most recently, Cheragh-Birjandi et al [37] postulated that 10 Mediators of Inflammation in turn promote the expression of a variety of matrixdegrading enzymes, including metalloproteinases (MMPs) [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vivo and in vitro studies [36,37] have shown that CUR treatment reduces iNOS production in various inflammatory diseases. Most recently, Cheragh-Birjandi et al [37] postulated that 10 Mediators of Inflammation in turn promote the expression of a variety of matrixdegrading enzymes, including metalloproteinases (MMPs) [38][39][40]. In the early stage of OA, high upregulation of MMP-13 expression, a prominent catabolic enzyme, leads to severe deterioration of cartilage as it induces type II collagen, which is a reason for nearly 90% of the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological microenvironments can be modulated or influenced by curcumin and FCE. Curcumin can inhibit the production of inflammatory mediators such as nitric oxide (NO), prostaglandin2 (PGE2), IL-6, and IL-8 stimulated by IL-1β [11,12,38]. Additionally, curcumin prevents IL-1β-induced NF-κB activation and translocation, giving rise to reduced expression of the NF-κB downstream pro-inflammatory gene COX-2 [39].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it was concluded that curcumin can be an alternate cure in patients with knee osteoarthritis who cannot tolerate the adverse effects of nonsteroidal anti‐inflammatory drugs (NSAIDs) (Shep, Khanwelkar, Gade, & Karad, 2019). The data of another clinical trial displayed that nano curcumin supplementation (1,000 mg/day, 16 weeks) might be a potent method to attenuate the amounts of inflammatory markers including nitric oxide (NO) and collagenase‐2 in synovial fluids of patients suffering from knee osteoarthritis (Cheragh‐Birjandi et al, 2020). In another double‐blind randomized placebo trial conducted on 72 older adults with knee pain associated with osteoarthritis, curcumin 5% ointment twice daily for 6 weeks, significantly decreased the mean pain intensity (Jamali, Adib‐Hajbaghery, & Soleimani, 2020).…”
Section: Inflammationmentioning
confidence: 99%